Underrepresented and Underserved Populations in Neurological Research - Windon, Charles C.; Jackson, Ashley J.; Aguirre, Gloria A.; Tucker, Miwa; Amuiri, Alinda; Hill-Jarrett, Tanisha; Chen, Miranda; Pina Escuedro, Stefanie D.; Lieu, Kevin; Lopez, Lucia; Mei, Diana; Tee, Boon Lead; Watson, Caitlin W.; Agwu, Chidera; Kramer, Joel; Lanata, Serggio (Seminars in Neurology, 2024)
Underserved and underrepresented populations have historically been excluded from neurological research. This lack of representation has implications for translation of research findings into clinical practice given the impact of social determinants of health on neurological disease risk, progression, and outcomes. Lack of inclusion in research is driven by individual-, investigator-, and study-level barriers as well as larger systemic injustices (e.g., structural racism, discriminatory practices). Although strategies to increase inclusion of underserved and underrepresented populations have been put forth, numerous questions remain about the most effective methodology. In this article, we highlight inclusivity patterns and gaps among the most common neurological conditions and propose best practices informed by our own experiences in engagement of local community organizations and collaboration efforts to increase underserved and underrepresented population participation in neurological research.
Keywords: recruitment; community; underrepresented; underserved; research